A Case Report on Recurrent Dermatofibrosarcoma protuberans (DFSP), Successful Surgical Excision is Treatment of Choice - Arshadullah Khan; Sumayya Tajwar (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
A 23-years-old male patient came to the Surgical Oncology clinic in Saudi National Hospital, Makkah with complaint of non-healing wound present on the medial side of the right thigh since three months. A detailed history wastaken and it was revealed that this was a fast growing lesion and recurred im- mediate after surgical excision. The previous surgery had been carried out three months back in India. On the clinical examination it was revealed that it wasan irregular, ill-defined lesion, hard  in  consistency, not adherent to the underlying structures, and hence highly suspicious of malignancy. Diagnostic workups were done including  biopsy,  metastatic  workup  including  computer  tomography  (CT) scan chest abdomen and pelvis. On the basis of histopathology, it was diagnosed as dermatofi- brosarcoma protuberans (DFSP). The case was presented in the Sarcoma  Tumour  Board  and  ac-  cording to Tumour Board's recommendation, surgical excision was conducted.Patient was sent for anaesthesia assessment and  after  complete  blood  workup,  and  pre-anaesthesia  assessment,  pa-   tient was booked for elective resection of tumour. The tumour was successfully excised with all negative margins confirmed on the frozen section and finally the sample was sent for histopathology. Post-excision, patient was followed in surgical oncology clinic for local and systemic recurrence and it was concluded after three years follow-up, that there was no local and systemic recurrence. The dermatofibrosarcoma has high potential for local recurrence and  surgical  excision  with  2  cm  negative margins is the treatment of choice without adjuvant radiotherapy.